1994
DOI: 10.1007/bf02849098
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and potassium fertilization of potatoes: Sugars and starch

Abstract: Considerable evidence exists that both N and K influence potato (Solanum tuberosum L.) yields and quality. The impact of nutrients on tuber quality parameters under field conditions should be identified so optimum management practices can be utilized. We evaluated the N and K fertilization by Ksources effects on concentrations of nutrients, reducing sugars, sucrose and starch in the stem and apical tuber ends from two irrigated field experiments with the Russet Burbank cultivar. Nitrogen rates of 0, 112, 224 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0
12

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 24 publications
10
47
0
12
Order By: Relevance
“…Both petiole NO 3-N and K concentrations were both related to yields and SG but complex interactions appeared to obscure their relationships. Other papers have addressed the N and K rates, and K-source effects on petiole and tuber chemistries (7,25).…”
Section: Resultsmentioning
confidence: 99%
“…Both petiole NO 3-N and K concentrations were both related to yields and SG but complex interactions appeared to obscure their relationships. Other papers have addressed the N and K rates, and K-source effects on petiole and tuber chemistries (7,25).…”
Section: Resultsmentioning
confidence: 99%
“…In general, cultural practices were as recommended by the University of Idaho for potato production (Anonymous 1986;Bishop et al 1982;Kleinkopf et al 1981;Ohms 1962;Westermann et al 1994). Foliar sprays of either mancozeb at 1.8 kg ha-' or chlorothalonil at 1.25 kg ha-' were applied at weekly intervals between mid-July and 1 September to protect against foliar diseases (early blight and black dot) that can reduce yield (Anonymous 1986;Mohan et al 1992).…”
Section: Biomass Field Study With Sudangrass (Roots Vs Foliage)-expermentioning
confidence: 99%
“…However, the potato gave optimum tuber yield when N fertilizer was applied at the rate of 204 kg/ha and yield reduction was noted when applied above this rate [26]. There was also decrease in the dry matter beyond 200 kg N/ha, which might be due to difference in relative maturity of tubers [27]. The results of the experiment conducted by Georgakis et al during the year 1997 showed that increase in nitrogen rates up to favorite point led to increase in tuber yield per unit area beyond which the rate decrease [28].…”
mentioning
confidence: 97%